Comparative Study on the British Colonial School Buildings in Old Calabar (Nigeria) and Famagusta (North Cyprus) - Ukabi, Ejeng (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
British Colonial Period in various colonies in the world exerted impacts on the total life of the colonized, showing in physical layout modifications, socio-political institutional structures, economic and infrastructural development dimensions of the settlements. Schools in British Period served as Imperial syndicate to enforce compliance through formal education, community meeting place and centers for extra-curricular activities. The school buildings stood as icon and heritage assets in their locations with measures of both tangible and intangible heritage values. They also represent the Colonial Architecture of British Empire that shows hybridization of local and modern stylistic approaches and box philosophy of design. Today their historical, architectural, environmental and educational significance should construe the evidence for registering and preserving them for future generations. This research aims to compare the school buildings of the British colonial period in Old Calabar, Nigeria and Famagusta, North Cyprus. The methodology of the thesis is qualitative method, firstly via literature reviews of the keywords of the thesis title. Secondly, through case study that entails field survey to make selection based on the school buildings that were built during British Period in Old Calabar, Nigeria (1885-1960) and Famagusta, North Cyprus (1878-1960). The field study area will be limited to the 2 Local Government Areas in Calabar and 13 districts in Famagusta. The case study involves historic analysis and physical analysis of the selected cases that will be supported by observations, photographs and measurements to achieve the stated aims. In order to appreciate the physical characteristics of the buildings their architectural assessment will be limited to the spatial organization, formal organization, architectural details, building materials and structural system of each case. This thesis has five Chapters. Chapter 1 introduces the need for studying the subject and background of the study. Chapter 2 includes the theoretical framework through literature review of British Colonial Architecture and Colonial schools. The British Colonial Period in Calabar and Famagusta will be discussed in Chapter 3. The analysis of the selected school buildings and the findings on the comparison of the school buildings of the two regions will be given in Chapter 4, regarding their architectural assessments’ outcome. Chapter 5 takes up the conclusion of the thesis. The findings generated proves that linear spatial organization, load bearing structural system, repetition of spaces with similar functions, use of materials like (stones, wood, metal, glass and concrete) constitute the similarities between the schools. Differences occurs in the arcades form, roof form and slope and the wall thickness between two context’s school structures. For the differences, Calabar school buildings show repetition of arcaded/straight terraces, steep roof slopes and slender stone walls while Famagusta ones show repetition of arcades with straight post and lintel character, flat/gentle roof slopes and massive stone walls due to the contrasting climatic conditions. Keywords: British Colonial period, British Colonial architecture, school buildings, Old Calabar, Famagusta.

ÖZ : İngiliz Koloni Dönemi ınin birçok koloni ülkesinin fiziksel gelişimleri, sosyo-politik ve yönetimsel alanlarda, ekonomik ve altyapı gibi alanlarda geniş etkileri olmuştur. İngiliz dönemi okulları, İngiliz standartlarında şirketleşmeyi hedefleyen bir eğitim şeklinde hizmet vermiş ve aynı zamanda halkların toplanma yeri yanında birçok eğitim aktivitesini gerçekleştirme yerleri idiler. Okul binaları, koloni döneminin yerel ve modern mimari sentezi olarak kabul gören ‘kutu’ biçimindeki tasarımları nedeni ile birer ikon ve kültürel değer olarak görülebilirler. Bu okulların mimari, tarihi, çevresel ve bilimsel değerleri, onların listelenmesini ve gelecek nesillere korunarak aktarılmasını gerektirir. Bu çalışma İngiliz Koloni dönemi okullarının Old Calabar- Nijerya ve Mağusa-Kuzey Kıbrıs örneklerinin karşılatırılmalı olarak incelenmesini hedeflemektedir. Tezde niteliksel araştırma methodu kullanılmıştır. İlk önce tezin anahtar sözcükleri ile ilgili literatür taraması yapılmıştır. İkinci olarak tezin çalışma alanı olarak seçilen Old Calabar, Nijerya (1885-1960) ve Mağusa Kuzey Kıbrıs (1878-1960)’daki İngiliz koloni dönemi okulları seçilmiştir. Çalışma alanı Nijerya’nın iki yerel yönetim bölgesi ile Mağusa’nın 13 bölgesindeki okulları kapsamaktadır. Alan çalışması tarihi ve mimari analizler yanında gözlemler, fotoğraflar ve çizimlerle desteklenmiştir. Okul yapılarının fiziksel özelliklerini saptamak için yapılan mimari değerlendirme mekansal organizasyon, formal organizasyon, mimari detaylar, bina elemanları ve stürüktürel sistem analizlerini içermektedir. Tez beş bölümden oluşmaktadır. Birinci bölüm bu konunun çalışma nedeni, çalışmanın amacı ve metodunu tartışmaktadır. İkinci bölüm İngiliz Koloni dönemi mimarisi ve okulları ile ilgili literature çalışmasını içermektedir. Nijerya ve Kuzen Kıbrıs’taki İngiliz Koloni dönemi üçüncü bölümde irdelenmiştir. Alan çalışması için seçlen okulların analizleri ve analizlerden elde edilen sonuçlar karşılaştırılmalı olarak dördüncü bölümde verilmektedir. Beşinci bölüm çalışmanın sonuçunu içermektedir. Yapılan analizler sonucunda her iki çalışma alanındaki İngiliz Koloni dönemi okullarının benzer mimari özellikleri şu şekilde soptanmıştır: lineer mekansal organizasyon, yığma stürüktür systemi, aynı fonksiyona sahip mekanların yanyana sıralanması, yerel malzeme kullanımı (taş, ahşap, metal, cam ve betonarme). Farklılıklar ise binalan çatı, arkad ve duvar kalınlıklarında ortaya çıkmaktadır. Buna göre Calabardaki okul yapılarında kemerli ve düz arkadlar, eğimli çatı ve ince taş duvarlar kullanılmışken, Mağusa okullarında düz kolon kirişleri olan arkadlar, az eğimli veya düz çatılar ile kalın taş duvarlar bölgelerin farklı iklim koşullarına göre tercih edilmiçtir. Anahtar sözcükler: İngiliz Koloni Dönemi, İngiliz Koloni Mimarisi, okul yapıları, Old Calabar, Mağusa.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2015. Supervisor: Assoc. Prof. Dr. Beser Oktay Vehbi.
Keywords: Architecture; School Buildings - Architecture - Old Calabar (Nigeria) - Famagusta (Cyprus, North); British Colonial period; British Colonial architecture; school buildings; Old Calabar; Famagusta